Corporate governance and its impact on the performance of firms in emerging countries: The evidence from Vietnam - Thang, Nguyen Ngoc (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 27 No 5E, 2011)
Abstract. Corporate governance has been become an important issue for both Vietnamese firms and government. This study examines the effects of corporate governance on firm performance in Vietnam using the 2009 Survey of Corporate Governance Practices, which surveyed a sample of 100 large, publicly traded Vietnamese companies on the Hanoi Stock Exchange (HSE) and the Ho Chi Minh Stock Exchange (HOSE) on 1 st January 2009. The research results show that corporate governance has an impact on firm performance. More specifically, corporate governance practices have impacted on firm profitability and market performance. The article concludes with some recommendations for management and directions for future research.   Keywords: Corporate governance, firm performance, emerging countries, Vietnam.